Additive manufacturing of Ti-6Al-4V horizontal hollow struts with submillimetre wall thickness by laser powder bed fusion. (October 2022) - Noronha, J.; Qian, M.; Leary, M.; Kyriakou, E.; Almalki, A.; Brudler, S.; Brandt, M.
Abstract: Efficient lattice unit cell topologies often necessitate the manufacture of unsupported horizontal struts. The fabrication of unsupported horizontal struts by laser powder bed fusion (LPBF) is inherently challenging, where the associated research data is limited for solid or dense cross-sections while no data exists for hollow struts. By examining LPBF-fabricated Ti-6Al-4V hollow struts of various diameters and wall thicknesses over increasing span lengths, a robust LPBF additive manufacturability range has been established for Ti-6Al-4V hollow struts. To achieve successful fabrication, three laser scan strategies were explored, proposed, and systematically compared. Horizontal solid struts and vertical hollow struts of equivalent diameters (and wall thickness) were similarly assessed over the same span lengths as comparators to quantify the manufacturability. This research provides previously unavailable design data, required for LPBF additive manufacturing of lattices with horizontal strut elements. Highlights: Ti-6Al-4V horizontal hollow and solid struts were successfully manufactured at a submillimetre wall thickness. The manufactured hollow struts achieved a low frequency of defects, enabling the establishment of acceptable LPBF guidelines. Unique laser scan strategies were implemented for a range of wall thicknesses, strut diameters, and unsupported span lengths. The experimental findings expand the capabilities of LPBF for thin walled structures.